2022
DOI: 10.1016/j.idh.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected benefit of COVID-19 hospital restrictions: Reduction in patients isolating with multidrug resistant organisms after restrictions were lifted

Abstract: Background During the COVID-19 pandemic, measures to prevent microorganism transmission were implemented across hospitals, including wearing compulsory surgical masks, minimising non-urgent procedures and restricting visitors. Previously, concerns have been raised that MRO-associated deaths could rise during a future pandemic through superimposed bacterial infections, inappropriate antibiotic use and reduced focus on preventing MRO infections. Methods In the state of Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…Em contrapartida, quatro dos artigos analisados nesta revisão tiveram como resultados de seus estudos um decréscimo na identificação de microrganismos multirresistentes quando comparados os períodos pré-pandêmico e pandêmico (ELLIOTT et al, 2022;BENTIVEGNA et al, 2021;FU et al, 2021;KARATAS et al, 2021). Esse cenário pode ser justificado pelo fato de que ocorreu uma mudança nos hábitos sociais como o da utilização de máscaras, higienização das mãos e redução de grandes aglomerações de pessoas durante a pandemia (GALVÃO et al, 2020).…”
Section: Discussionunclassified
“…Em contrapartida, quatro dos artigos analisados nesta revisão tiveram como resultados de seus estudos um decréscimo na identificação de microrganismos multirresistentes quando comparados os períodos pré-pandêmico e pandêmico (ELLIOTT et al, 2022;BENTIVEGNA et al, 2021;FU et al, 2021;KARATAS et al, 2021). Esse cenário pode ser justificado pelo fato de que ocorreu uma mudança nos hábitos sociais como o da utilização de máscaras, higienização das mãos e redução de grandes aglomerações de pessoas durante a pandemia (GALVÃO et al, 2020).…”
Section: Discussionunclassified
“…The increase in MDR-GNB BSIs reported by Amarsy et al [11 ▪ ] coincided with a 131–148% increase in consumption of third-generation cephalosporins and represents one of the few studies that reported concurrent variation in antibiotic use [11 ▪ ,12 ▪ ,15,21,27,28]. Conversely, a decrease in these pathogens was recorded in mostly single centres in Australia [29], Italy [20,28], Sweden [30] and the US [31] by a magnitude of up to 20%.…”
Section: Variation In Antibiotic-resistant Gram-negative Infections B...mentioning
confidence: 93%
“…Whereas Amarsy et al [11 & ], in the network of 25 hospitals in Paris similarly recorded a 3.3-and 2.7-fold increase in ESBL-producing K. pneumoniae and ampicillinase C (AmpC)-producing Enterobacterales BSIs/100 hospitalised patients, respectively, other studies did not show any significant differences between pre and post pandemic periods [13 ] coincided with a 131-148% increase in consumption of third-generation cephalosporins and represents one of the few studies that reported concurrent variation in antibiotic use [11 ,12 & ,15,21,27,28]. Conversely, a decrease in these pathogens was recorded in mostly single centres in Australia [29], Italy [20,28], Sweden [30] and the US [31] by a magnitude of up to 20%.…”
Section: Extended-spectrum B-lactamase or Ampc Producing Enterobacter...mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of MDR bacteria within hospital settings poses a significant threat that extends to the selection of empiric antibiotics that target MDR bacteria. This can perpetuate a vicious cycle of increasing antimicrobial resistance [ 2 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%